THE EFFECT OF WARM GINGER COMPRESS TOWARDS JOINT PAIN OF THE ELDERLY AT UPT PANTI WERDHA MOJOPAHIT, MOJOKERTO DISTRICT - Puteri Indah Dwipayanti; Anik Supriani; Nanik Nur Rosyidah; Nurul Mufida (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2018)
Background: There was joint pain that frequently happens by the elderly, which was joint pain. One of actions to abate the joint pain was compress with warm ginger.Objectives: The aims of this research were to identify the effect of warm ginger compress towards joint pain of the elderly at UPT Panti Werdha Mojopahit, Mojokerto District.Method: Design of this research was Pre-Experiment with Type of one group pre-test-post test design. Population of this research was whole of elderly who undergoes joint pain at UPT Panti Werdha Mojopahit Mojokerto district. Technique that used to take sample in this research was purposive sampling with 20 respondents. Data collecting was done before and after warm ginger compress was given use pain scale instrument PAINAD with 1-10 scale. The researcher used Wilcoxon statistic test with value of α=0, 05 to analyze the data.Results: The result of this research wasgained before carried out by warm ginger compress with advance pain scale of 6 respondents (30%), and intermediate pain scale of 10 respondents (50%). After the warm ginger compress was done by 8 respondents (40%) with light pain scale and 11 respondents (55%) with intermediate pain. Data analyzing used statistic test with Wilcoxon P value test 0,003 (α˂ 0, 05). It showed that warm ginger compress effective towards joint pain of the elderly.Conclusion: Looking at the result above shows that warm ginger compress can be created as one of alternative choices to decrease joint pain intensity of the elderly, because this non-pharmacologist treatment uses easy to be obtained ingredient and there is no side effect for the elderly.Key words: Joint Pain, Warm Ginger Compress, Elderly.